2011
DOI: 10.5943/cream/1/2/1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of secondary metabolites in the Xylariaceae as parameters for

Abstract: This paper constitutes a synopsis of our polythetic studies of the Xylariaceae, which was originally compiled in the course of a Habilitation thesis. Based on several thousands of specimens and several hundreds of cultures, morphological studies of the teleomorphs and anamorphs of these fungi were combined with chemotaxonomic studies based on HPLC-DAD/MS profiling, as well as PCR fingerprinting and molecular phylogenetic analyses. Numerous novel pigments and other natural products, many of which were shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 138 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…It is well-known that squirrels can detect hypogeous sporocarps by smell [47,48]. Xylariaceous ascomycetes effuse a variety of volatiles, depending on the developmental stage of their sporocarps [49], which may be detected by squirrels. McKeever [47] also reported that fungi constitute the largest portion of squirrel diets, particularly in the…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that squirrels can detect hypogeous sporocarps by smell [47,48]. Xylariaceous ascomycetes effuse a variety of volatiles, depending on the developmental stage of their sporocarps [49], which may be detected by squirrels. McKeever [47] also reported that fungi constitute the largest portion of squirrel diets, particularly in the…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that squirrels can detect hypogeous sporocarps by smell [47,48]. Xylariaceous ascomycetes effuse a variety of volatiles, depending on the developmental stage of their sporocarps [49], which may be detected by squirrels. McKeever [47] also reported that fungi constitute the largest portion of squirrel diets, particularly in the summer and early autumn, and represent the second largest portion of their diets in the early spring; however, the majority of the fungi eaten by squirrels may be basidiomycetes [48].…”
Section: Discussionmentioning
confidence: 99%
“…Biscogniauxia is a fungal genus belonging to the family Graphostromataceae, the order Xylariales and the class Sordariomycetes. These fungi are renowned as cosmopolitan and omnipresent wood decomposers, as well as prevalent endophytes [29]. The Biscogniauxia genus (basionym Nummularia Tul.…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomy of this genus is based on morphological characters, colour of stromatal pigments, secondary metabolites, anamorph structures and molecular methods (Stadler et al, 2001(Stadler et al, , 2014Guidot et al, 2003;Stadler, 2011;Helay et al, 2018). The anamorphic structures are most often referred to as the genus Nodulisporium Preuss that produces conidia from percurrent proliferating conidiogenous cells (Petrini, Müller, 1986;You et al, 1997).…”
Section: Introductionmentioning
confidence: 99%